PENGEMBANGAN BUKU AJAR NAHWU BERBASIS THARIQOH MA’RIFIYAH DI MADRASAH DINIYAH DARUL MUTTAQIN JOMBANG - Shofiyani, Amrini; Nafingah, Nafingah (JoEMS (Journal of Education and Management Studies), 2021)
This research is motivated by the lack of understanding of the students' level of nahwu rules. With that, this study has the aim of developing nahwu teaching materials based on thariqoh ma’rifiyah as a solution to overcome these problems. The method used in this research is R&D using Borg and Gall development. This research will produce results in the form of an imrithi roaming textbook. The results of data analysis stated that the developed textbooks were able to improve students' learning outcomes in nahwu lessons which went hand in hand with increasing their understanding. This increase has a great influence as a solution to minimize the level of students' misunderstanding. Learning using nahwu textbooks with the thariqoh ma’rigiyah method on nahwu subjects, can distinguish the average value of learning outcomes. This can be shown from the results of calculations using the paired t-test, the results obtained with t-count 15.24 t-count > t-table of 0.0225. The results of the pretest learning of students are 55, and posttest are 80. So it can be concluded that H0 is rejected and H1 is accepted. That is, learning using nahwu textbooks with the thariqoh ma’rifiyah method is more effective than the previous learning.